(untitled) (Journal of the College of Basic Education, 2022)
The work is based on the design of the fabrics on the basis of its use of the forces of the elements, which in turn lead to Diversity and contrast from one design to another because of its impressive efficacy, which lies between the difference in the establishment of the unit Design constructivism and diversity of thought, style, methods, systems... but they basically come in accordance with Verified The design work unit is directed in a specific direction called for by the functional necessity of use. It is a kind of conscious constructive process in which the designer’s mind controls the mechanisms of organization and installation.